PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PADA KEPUASAN KERJA YANG BERDAMPAK TERHADAP KINERJA KARYAWAN PT. MADU BARU BANTUL, YOGYAKARTA - Erlangga Arya Mandala; Faresti Nurdiana Dihan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The Emotional intelligence, spiritual intelligence and job satisfaction to be part of the factors that influence performance. The purpose of this study was to determine the effect of emotional intelligence and spiritual intelligence on the performance through job satisfaction as an intervening variable partially and simultaneously. This study also aimed to determine the effect of emotional intelligence and spiritual intelligence on the performance through job satisfaction as an intervening variable directly and indirectly. This study was conducted to 77 respondents employees of PT. Madu Baru, Yogyakarta. The research method used is quantitative method uses statistical analysis and descriptive. The results of this study are (1) there is a significant effect of emotional intelligence on employee job satisfaction. (2) there is a significant influence of spiritual intelligence on employee job satisfaction. (3) There is a significant relationship between emotional intelligence and spiritual intelligence on job satisfaction. (4) There is a significant relationship between emotional intelligence on employee performance. (5) There is a significant relationship between spiritual intelligence on employee performance. (6) There is a significant relationship between emotional intelligence and spiritual intelligence on employee performance. (7) There is a significant relationship between job satisfaction on employee performance. (8) There is an indirect effect of emotional intelligence on the performance of employees through job satisfaction. (9) There is the indirect influence of spiritual intelligence on the performance of employees through job satisfaction.